2016
DOI: 10.1016/j.molimm.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of CXC chemokines modulation in brown trout ( Salmo trutta ) following infection with a bacterial or viral pathogen

Abstract: Chemokine modulation in response to pathogens still needs to be fully characterised in fish, in view of the recently described novel chemokines present. This paper reports the first comparative study of CXC chemokine genes transcription in salmonids (brown trout), with a particular focus on the fish specific CXC chemokines (CXCL_F). Adopting new primer sets, optimised to specifically target mRNA, a RT-qPCR gene screening was carried out. Constitutive gene expression was assessed first in six tissues from SPF b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…IFN-γ expression was found to be highly induced by both bacterial and viral systemic infections, respectively, caused by Piscine novirhabdovirus and Yersinia ruckeri, in brown trout (Salmo trutta). During these infections, the transcription of IFN-γ was highly correlated to the bacterial and viral load in both spleen and kidney together with a strong correlation to the expression of an array of CXC chemokines, including CXCL8 or IL-8 [52,53]. Moreover, the other antiviral response markers selected for this study in red tilapia, including irf-3, Mx, and VIPERIN (or rsad-2), were previously found to be strongly induced during several viral infections in other teleosts [54][55][56] and involved in the IFN response in tilapia [57].…”
Section: Discussionmentioning
confidence: 99%
“…IFN-γ expression was found to be highly induced by both bacterial and viral systemic infections, respectively, caused by Piscine novirhabdovirus and Yersinia ruckeri, in brown trout (Salmo trutta). During these infections, the transcription of IFN-γ was highly correlated to the bacterial and viral load in both spleen and kidney together with a strong correlation to the expression of an array of CXC chemokines, including CXCL8 or IL-8 [52,53]. Moreover, the other antiviral response markers selected for this study in red tilapia, including irf-3, Mx, and VIPERIN (or rsad-2), were previously found to be strongly induced during several viral infections in other teleosts [54][55][56] and involved in the IFN response in tilapia [57].…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was manually extracted from 100 mg of each intestinal sample from each group (control, SeNPs0.75, SeNPs1.5) using a handheld homogenizer to homogenize the tissue immersed in one mL Genzol™ (Geneaid Biotech Ltd., Taiwan) without DNase treatment. The pellet was dissolved in TE buffer (pH 8.0) as described previously [ 40 ]. The RNA quantity was estimated using a NanoDrop spectrophotometer (Q5000/Quawell, Massachusetts, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was manually extracted from 100 mg of the anterior kidney using a handheld homogenizer to disperse the tissue immersed in one mL of Genzol TM (Geneaid Biotech Ltd, Taiwan) without DNase treatment. The pellet was dissolved in TE buffer (pH 8.0) as described previously [ 40 ]. The RNA quantity was estimated using a Nanodrop spectrophotometer (Q5000/Quawell, Massachusetts, USA).…”
Section: Methodsmentioning
confidence: 99%